DEVELOPMENT OF SPARKOL VIDEOSCRIBE-BASED LEARNING MEDIA USING THE ADDIE MODEL FOR VOCATIONAL TOURISM EDUCATION: A FEASIBILITY AND EFFECTIVENESS STUDY - Lutfita Yona Wijayanti; Fahrur Rozi (JoEICT (Jurnal of Education And ICT), 2025)
The integration of digital media in vocational education remains underexplored, particularly in the context of tourism subjects at the secondary vocational level. Conventional instructional methods—such as dictation, static PowerPoint presentations, and paper-based assignments—have been widely reported to reduce student engagement and learning motivation. This study addresses this gap by developing and evaluating Sparkol VideoScribe-based animated whiteboard learning media for the Productive Tourism subject at Grade X of SMK Negeri 1 Boyolangu, Tulungagung, Indonesia. The ADDIE instructional design model (Analysis, Design, Development, Implementation, and Evaluation) was employed as the systematic development framework. Feasibility was assessed through expert validation and user trials. A Media Expert validated the product and awarded a score of 83% (Very Feasible), while a Content Expert assigned 87.5% (Very Feasible). Small-group trials (n = 5) yielded 77.6% (Very Feasible), and large-group trials (n = 20) produced 90% (Very Feasible), resulting in an overall mean feasibility score of 84.5%. These findings demonstrate that Sparkol VideoScribe-based media represents a technically sound and pedagogically appropriate learning tool for vocational tourism education. The novelty of this research lies in its systematic application of the ADDIE framework to develop whiteboard animation media specifically contextualized for hospitality and tourism competencies in Indonesian vocational secondary schools. Future research should examine the media's direct impact on student learning outcomes and explore adaptive integration with mobile and cloud-based learning environments